Elements of nature ecological and economic relations land ownership in the area of combating land degradation and desertification - Movchan, M. (Land Management, Cadastre and Land Monitoring, 2017)
In Ukraine, as in many other countries, developing land degradation is a serious problem. So, despite the fact that the scale of the problem indicated in the Strategy of Environmental Policy of Ukraine (2011), analysis of economic losses from land degradation to the national economy throughout the country almost was conducted.Measures to implement sustainable land use inUkraineis a national priority. Steps shall be taken to encourage land use management via policies as reflected in the concept of combating land degradation and desertification, and the National Action Plan to combat land degradation and desertification. Given the importance of the sustainable use of agricultural land to accelerate and sustain economic development inUkraine, based on the interests of the poor, there is an imminent need for a better understanding of the scale land degradation and benefits of land use management. Demonstration of the net economic benefits of land use management practices on existing evidence makes the development of policies in Ukraine in the use and protection of land for the development of the agricultural sector.In this regard, the proposed logical-semantic model components forming the essence of ecological and economic relations of land ownership rights in the fight against land degradation and desertification.Components of formation of ecology and economic relations of land ownership rights in the fight against land degradation and desertification are the conditions that influence the formation of ecology and economic relations of land rights in combating land degradation and desertification, the composition of lands and their quality status types of land forms and corresponding methods of land use, describing the ecological and economic relations of land ownership rights in the fight against land degradation and desertification, which prtsesi simulation defining ecological and economic land relations based on a set of rights to land and other natural resources : ownership, use, including lease, rent, superficies,Keywords: ecological and economic relations, property rights, land degradation and desertification.